2017
DOI: 10.1001/jamaoncol.2016.3015
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Comparison of Antibodies to Programmed Cell Death 1 Ligand 1

Abstract: Importance There are at least four immunohistochemistry assays for PD-L1 at various stages of interaction with the FDA as companion or complementary diagnostic tests for benefit from PD-1 axis therapies. The performance of each assay for selection of patients that respond to therapy has been published, but no data has been published that compares the assays to one another or to direct measurements of PD-L1. Objective To determine whether the antibody reagents are interchangeable, we quantitatively compared e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
130
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(144 citation statements)
references
References 16 publications
13
130
0
1
Order By: Relevance
“…In addition, these results should not be extrapolated to antibody clones embedded in other assay protocols unless these protocols are fully validated, and should also not be extrapolated to other cancer indications without a separate study. A recent, smaller scale study assessing the performance of different PD-L1 antibodies indicated good concordance between the 22C3, 28-8, and SP263 antibodies in detection of PD-L1 in cell lines and tumor samples (39), consistent with our study. In that study (39), locked assays were not used, and concordance depended on the staining protocol used, emphasizing the importance of ensuring all elements of an IHC protocol are properly validated.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, these results should not be extrapolated to antibody clones embedded in other assay protocols unless these protocols are fully validated, and should also not be extrapolated to other cancer indications without a separate study. A recent, smaller scale study assessing the performance of different PD-L1 antibodies indicated good concordance between the 22C3, 28-8, and SP263 antibodies in detection of PD-L1 in cell lines and tumor samples (39), consistent with our study. In that study (39), locked assays were not used, and concordance depended on the staining protocol used, emphasizing the importance of ensuring all elements of an IHC protocol are properly validated.…”
Section: Discussionsupporting
confidence: 91%
“…A study comparing the performance of four PD-L1 IHC antibodies, including 28-8, 22C3, E1L3N, and SP142, with their corresponding platforms showed that the SP142 antibody detected less PD-L1 expression in TCs and ICs in non-small cell lung cancer patient samples than the other antibodies did [27]. However, another study evaluating the performance of different anti-PD-L1 antibodies using optimal assay concentrations found a high concordance among different antibodies including SP142, suggesting that the variation among different PD-L1 IHC antibodies may be attributed to tumor heterogeneity, assay-or platform-specific variables [28]. In our study, when PD-L1 expression in 1% of TCs was used as a cut-off point, the positive rate (17.9%, 24/134) was comparable with the PD-L1 positive rate (16.6%, 36/217) reported in a previous study of HCC patient samples using E1L3N antibody [13].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study further suggested that the inherent tumor heterogeneity, or assay-or platform-specific variables may also contribute to the discordant results of these companion diagnostic tests. 43 These results suggest the challenges of extrapolating the results from one test to that of another test. This is reillustrated by Blueprint Chair Dr Fred Hirsch (professor of medicine at the University of Colorado), who said in an interview, ''when pathologists used each assay in combination with its own prescribed cutoff, the assays did sometimes disagree on whether samples were PD-L1-positive.''…”
Section: Strategies To Measure Pd-l1/pd-1 Expression Immunohistochemimentioning
confidence: 99%